Los conocimientos tradicionales y el régimen legal de acceso y distribución de beneficios - Zamudio, Teodora (2012)
Traditional knowledge and legal regime of access and benefitsdistributionThis work highlights interests around traditional knowledge access of local and indigenous communities stressing the need to establish institutions involved in order to give an efficient legal answer within the political, scientific and economic framework. The author critically reviews ideas developed about this issue among international, regional and local spheres formulating the thesis of application of customary law, in particular about prior informed consent and benefits-sharing. Without disregard present conflicts management and those envisaged in the near future, implications and scenarios where State and international organizations determination must face this subject are addressed.